Operationalization of Ngos Activities: Proposing an E-Social Network Model for Ngos Activities in Edo State, Nigeria. - Odita, A.O.; Victor, Ehiedu (Advances in Social Sciences Research Journal, 2015)
Abstract: In recent years, especially in developed countries, various systems have been created to advance the management and organization of the potentials and resource base of NGOs towards maximizing their benefits to the society. Such systems use the latest communications technology and electronic and digital resources, and have developed huge networking systems like SIGLE (System for Information on Grey Literature) and NTIS (National Technical Information Service) to distribute and manage the efforts of civil societies. Because of the scarcity of a global standardized organization system for information management and often limited access to computer technology, efficient management of information and development cooperation/interrelationship among NGOs is still seriously lacking, particularly in developing countries. Based on the impact assessment of registered NGOs in Edo State, Nigeria, this study proposes an e-social network model. This paper explains the current state of interactive relations among NGO organizations within the State, and stakeholders and actors in development interventions, then assesses their needs for a networking system, and finally recommends a functional electronic network model for the operationalization of their development activities to meet today’s global challenges. Keywords: Networking, E-communication, Information management, Community Development